Theoretical modeling and experimental validation of hydrodynamic cavitation reactor with a Venturi tube for sugarcane bagasse pretreatment - Bimestre, Thiago Averaldo [UNESP] (2020)
A hydrodynamic cavitation reactor with a Venturi tube was modeled through a computational fluid dynamics approach in order to evaluate the influence of pressure ratio, diameter and length of the throat zone. A cavitation reactor equipped with a Venturi tube was built in accordance with the computational modeling results. Hydrodynamic cavitation assisted alkaline pretreatment was performed to evaluate the influence of NaOH concentration (1–5%), the weight to volume percentage of solid in liquid (1–5%) and the reaction time (20–60 min.) in the lignin removal. The response surface methodology was used to optimize pretreatment parameters for maximum lignin removal. The optimal condition was 4.90% of NaOH and a solid weight percentage in liquid of 2.03% in 58.33 min, resulting in a maximum removal of 56.01% of lignin. Hydrodynamic cavitation can be easy to employ, an efficient and promissory pretreatment tool.